1994
DOI: 10.3109/00016349409013461
|View full text |Cite
|
Sign up to set email alerts
|

The relationshp of clinical‐pathologic status and adiuvant treatment with natural hller cell activity in stage I and II endometrial carcinoma

Abstract: I(.I(I Oh.v/er Gjwecol Scmd 1994: 73: 652-657. (ij Acta Obstet Gynecol Scand 1994Ohjwriw. The aim of our study was to evaluate the basal immune reactivity in patients with locally advanced endometrial carcinoma, and the immune modulating effect of adjuvant treatment in cancer population randomized to endocrine or radiation therapy. M t r /~r . ; d otitl t w k o d s . Forty-three patients with F I G 0 stage I and II endometrial carcinoma, treated with primary radical surgery, were randomly selected to receive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In particular, radiotherapy has been shown to cause significant reductions in both NK cell cytolytic activity in breast carcinoma survivors24 and the number of NK cells (CD3–CD16+CD56+) in colorectal carcinoma survivors 25. Similarly, Garzetti et al reported that Stages I and II endometrial carcinoma survivors who received radiotherapy demonstrated a significant reduction in NK cell cytolytic activity 26. Squamous cell lung carcinoma survivors who received radiotherapy have been shown to have significant reductions in the total number of lymphocyte, T cells (CD4+, CD8+), and T cell proliferation in response to mitogenic stimulation 27.…”
Section: Immune System Response To Tumorsmentioning
confidence: 97%
“…In particular, radiotherapy has been shown to cause significant reductions in both NK cell cytolytic activity in breast carcinoma survivors24 and the number of NK cells (CD3–CD16+CD56+) in colorectal carcinoma survivors 25. Similarly, Garzetti et al reported that Stages I and II endometrial carcinoma survivors who received radiotherapy demonstrated a significant reduction in NK cell cytolytic activity 26. Squamous cell lung carcinoma survivors who received radiotherapy have been shown to have significant reductions in the total number of lymphocyte, T cells (CD4+, CD8+), and T cell proliferation in response to mitogenic stimulation 27.…”
Section: Immune System Response To Tumorsmentioning
confidence: 97%
“…An increased number of CD8 + CTLs at the border of endometrial carcinomas have been associated with improved survival [6]. In contrast, only a small number of NK cells are present in endometrial carcinomas, and decreased cytotoxic activity of NK cells isolated from the peripheral blood of patients with endometrial carcinoma has been reported [7,8].…”
Section: Introductionmentioning
confidence: 94%
“…NK cell activation is impaired in the tumor microenvironment, including the EC microenvironment. Garzetti et al (35) suggested that locally advanced stage I and II ECs had significantly lower mean values of NK cell activity compared with healthy controls. Furthermore, a decrease in NK cell activity increased the depth of myometrial tumor invasion (35).…”
Section: Regulatory T Cells (Tregs)mentioning
confidence: 99%
“…Garzetti et al (35) suggested that locally advanced stage I and II ECs had significantly lower mean values of NK cell activity compared with healthy controls. Furthermore, a decrease in NK cell activity increased the depth of myometrial tumor invasion (35). NK cell activity also diminished with increased nuclear grade in stage I EC.…”
Section: Regulatory T Cells (Tregs)mentioning
confidence: 99%